2012
DOI: 10.1161/circresaha.111.249482
|View full text |Cite
|
Sign up to set email alerts
|

Dominant-Negative Control of cAMP-Dependent I Ks Upregulation in Human Long-QT Syndrome Type 1

Abstract: Rationale:The mutation A341V in the S6 transmembrane segment of KCNQ1, the ␣-subunit of the slowly activating delayed-rectifier K ؉ (I Ks ) channel, predisposes to a severe long-QT1 syndrome with sympathetictriggered ventricular tachyarrhythmias and sudden cardiac death.Objective: Several genetic risk modifiers have been identified in A341V patients, but the molecular mechanisms underlying the pronounced repolarization phenotype, particularly during ␤-adrenergic receptor stimulation, remain unclear. We aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 34 publications
1
49
0
Order By: Relevance
“…The LQT1 mutation A341V in KCNQ1 segment 6 has recently been shown to preserve the KCNQ1-yotiao interaction but to reduce cAMP-induced KCNQ1 phosphorylation at S27 and subsequent I KS current upregulation (Heijman et al, 2012). The LQT5 mutation D76N in KCNE1 C-terminus spared the cAMPmediated KCNQ1 phosphorylation at S27 but failed to upregulate its resulting I KS current.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LQT1 mutation A341V in KCNQ1 segment 6 has recently been shown to preserve the KCNQ1-yotiao interaction but to reduce cAMP-induced KCNQ1 phosphorylation at S27 and subsequent I KS current upregulation (Heijman et al, 2012). The LQT5 mutation D76N in KCNE1 C-terminus spared the cAMPmediated KCNQ1 phosphorylation at S27 but failed to upregulate its resulting I KS current.…”
Section: Discussionmentioning
confidence: 99%
“…8C). To date, only one LQT1 mutation A341V in KCNQ1 (Heijman et al, 2012) has been found to disrupt KCNQ1 phosphorylation at S27, while preserving the KCNQ1-yotiao interaction. Interestingly, the LQT5 mutant P127T has been described both as a single mutation (Splawski et al, 2000) and as being additionally associated with the LQT1 mutation A341V in another proband who presented with syncope and longer QTc interval than his parents (Westenskow et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…35 The observed VIP effects on repolarizing currents are consistent with the known consequences of cAMP/PKA signaling pathway activation. 36,37 However, it was unexpected that VIP suppresses I Na because activation of cAMP/PKA pathway would increase I Na .…”
Section: Molecular Basis Of Vip Effectsmentioning
confidence: 99%
“…This suggests an association with vagal mechanisms [5]. Moreover, the Iks channel is regulated by signals generated in the β-adrenergic receptor (β-AR) [6]; notably, KCNQ1 mutations impair the cellular response to β-adrenergic stimulation [7]. Also, it has been reported that β-adrenergic agonists and magnesium modulate Iks in frog cardiomyocytes [8].…”
Section: Introductionmentioning
confidence: 99%